PENAMPILAN AGRONOMI BERBAGAI AKSESI KATUK Sauropus androgynus (L.) Merr. PADA DOSIS PUPUK UREA BERBEDA - Ulfa Khaerunnisa; Arifah Rahayu; Yanyan Mulyaningsih (Universitas Djuanda Bogor, 2020)
Katuk Sauropus androgynus (L.) Merr is a leafy vegetable which requires nitrogen for itsvegetative growth. This study was aimed at assessing the agronomic performance of various accessions of katuk vegetable grown with different rates of urea fertilizer administration. A completely randomized design with two factors was used. The first factor was katuk accessions consisting of Sukaraja Sukabumi, Cugenang Cianjur, and Kemang Bogor. The second factor was urea fertilizer administration in five rates, namely 0, 33.3, 66.7, 100%, and 133.3% of recommended rate (R). Results showed that katuk plant of Sukabumi accession gave the best plant height and leaflet area. Katuk plant of Cianjur accession had the highest values of plant height, number of buds, yield fresh weight, yield dry weight, and root length. Katuk plant of Bogor accession was found to have the highest fresh root weight. Urea administration of 66.7-133.3% R resulted in katuk plant with the best values of plant height, number of buds, stem diameter. The widest leaf area was found in 100% R urea administration and the highest root weight was found in plants treated with 66.7% R urea administration. The increase of urea fertilizer doses starting from 33.3% R in Cianjur and Bogor katuk accession increased the total harvest wet weight and dry weight, while in Sukabumi accession the significant increase in production was at a dose of 100% R and 133.3% R urea. The increase in vitamin C content was significant in the application of 133.3% R urea fertilizer.